When Worldviews Collide: Linguistic Theory Meets Legal Semantics in United States v. X-Citement Video, Inc. - Craig Hoffman (Washington University Law Quarterly, 1995)
I would like to take a closer look here at how linguists and lawyers look at language (sentences) and how they build analyses in their own disciplines. I will then suggest how the more theoretical approach of linguists could be integrated with the more practical approach of lawyers.
Keywords: Linguistics; Law -- Interpretation & construction; Child pornography; United States v. X-Citement Video, Inc. 115 S. Ct. 464 (1994)